Microtutoring in higher education: the development and evaluation of a programme of skills - Shaw, Malcolm (1987)
The prime concern of the study is with the development and evaluation of a short in- service course suitable for teachers in Higher Education. The aim of the course is to introduce and allow tutors to practice the pedagogic skills relevant to encounters with students engaged in independent and individualised modes of teaching and learning such as assignments, projects, contract learning, practical work and research. The study is firmly grounded in principles reviews of staff development, theories derived from thorough of instruction, and microencounter theory and techniques. In exploring this novel area of study, the new generic term, microtutoring, is defined. The research approach is firmly based in the descriptive, case study, course evaluation tradition with some experimental research integrated within the overall design. A detailed description is given of the development of observable skills and the design of instruments for their detection and measurement. The clustering of skills into the meaningful and highly relevant dimensions of structure, directness, centredness, control, cognitive level and appropriateness is described. A full account is given of the formative evaluation of the course and the data and results derived from summative evaluation are processed and discussed. Further development and research in relation to both course and skills is identified and prioritised. Experimental results suggest that it is possible to cause significant changes to the tutorial skills, dimensions and style of a tutor in a predetermined direction. It also seems that these changes are independent of the extent of prior teaching experience possessed by the tutor.